Exploring the links between type and content of virtual background use during videoconferencing and videoconference fatigue - Li, Benjamin J.; Zhang, Heng (Frontiers in Psychology, 2024)
The popularity of remote working in recent years has led to a rise in the use of videoconferencing tools. However, these communication tools have also given rise to a phenomenon known as videoconference fatigue (VF). Using the limited capacity model of motivated mediated message processing and impression management theory as the theoretical framework, this study explores how different types and content of virtual backgrounds in videoconferencing influence people’s VF and well-being. A survey of 610 users of videoconferencing tools revealed significant variations in the content and type of virtual backgrounds used during videoconferences. Our findings highlight three main points: first, there is a significant relationship between the use of virtual backgrounds and VF; second, pairwise comparisons showed that the type of virtual background significantly influences the amount of VF experienced by users; third, the content of virtual backgrounds also significantly impacts the level of VF experienced by users. These results suggest that careful selection of virtual backgrounds can mitigate VF and improve user well-being. Theoretical and practical implications are discussed.